PEMANFAATAN BUAH PEDADA (Sonneratia caseolaris) DALAM PEMBUATAN MINUMAN INSTAN - Agung Surya Wiratno; Vonny Setiaries Johan; Faizah Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was to get the best ratio of sugar in making pedada fruit instant drink. Research used a to drink powder instant pedada fruit. The method used in this study was completely randomized design with 4 treatments and 4 replications. The treatment were GA1 (Sugar 70 : Extracts pedada 30), GA2 (Sugar 60 : 40 Extracts pedada), GA3 (Sugar 50 : Extracts pedada 50) and GA4 (Sugar 40 : Extracts pedada 60). The result showed that sugar ratio formulation significant effect on total sugar, total acid, yield, assessment of sensory descriptive colour parameters, flavor parameters assessment of hedonic states like instant pedada fruit. The best treatment was GA4 (Sugar 40 : extracts pedada 60) based on water content 1.71%, ash content 1.54%, total sugar 43.11%, yeald 67.15% and total acid 2.97%. Assessment of sensory and descriptive were colour is white, rather flavorful pedada fruit, acid, texture is rather smooth. Keyword : instant powder, pedada fruit, sugar